2010
DOI: 10.1007/s11517-010-0577-2
|View full text |Cite
|
Sign up to set email alerts
|

A technique based on laser Doppler flowmetry and photoplethysmography for simultaneously monitoring blood flow at different tissue depths

Abstract: The aim of this study was to validate a non-invasive optical probe for simultaneous blood flow measurement at different vascular depths combining three photoplethysmography (PPG) channels and laser Doppler flowmeter (LDF). Wavelengths of the PPG were near-infrared 810 nm with source-to-detector separation of 10 and 25 mm, and green 560 nm with source-to-detector separation of 4 mm. The probe is intended for clinical studies of pressure ulcer aetiology. The probe was placed over the trapezius muscle, and depths… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 30 publications
1
41
0
1
Order By: Relevance
“…By normalizing the modulation, and using wavelengths that have been found to better determine pulsatile blood flow, our present study demonstrated the practical application of a PPG device may be a promising technique as a heart rate monitor. 9,16,20,26,32 To our knowledge this is the first study to examine light wavelength reflectance and skin type influence during both rest and exercise.…”
Section: 36mentioning
confidence: 98%
See 2 more Smart Citations
“…By normalizing the modulation, and using wavelengths that have been found to better determine pulsatile blood flow, our present study demonstrated the practical application of a PPG device may be a promising technique as a heart rate monitor. 9,16,20,26,32 To our knowledge this is the first study to examine light wavelength reflectance and skin type influence during both rest and exercise.…”
Section: 36mentioning
confidence: 98%
“…6,16,49,50 The main concern with PPG technology for detection of pulse rate is related to the melanin concentration of the skin and its related pigmenting of skin. 3,20,50 Melanin is known to be highly absorbent to light, and thereby attenuating the incident light wavelength.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Повышение величины σ, как и значение величины Р М , может зависеть от раз-ных факторов. По мнению различных исследователей [7][8][9][10], рост значения σ может быть связан с более ин-тенсивным функционированием механизмов активно-го контроля. Кроме этого, большое влияние оказывает изменение сердечных и дыхательных ритмов в слу-чае патологии органов.…”
Section: Aw Lesnyh Ea Shimkounclassified
“…To give some insight onto the best-cited original papers, we selected the top ten from the periods 2008-2009 and 2010-2011. Out of these 20 papers, 7 are in the area of the circulation [8,9,15,20,24,25,27], 7 in the area of rehabilitation including brain computer interface [6,7,11,14,16,17,28], 2 related to sleep [19,35], 2 to tissue engineering and nanotechnology and 2 to electroporation [4,21]. Obviously the distribution of these subjects of publications are somewhat influenced by the special issues we had over this period [2,5,12,18,26,31,32].…”
mentioning
confidence: 99%